A Standard Study of the Impact of Total Productivity and Inflation on Nominal Wages during the Period (1985-2020) - Bardad, Torkia (Finance and Business Economies Review, 2022)
This study aimed to analyze a relationship between total productivity and inflation and nominal wages during the period 1985-2020 Through a standard study by applying an autoregressive model(ARDL) Where we divided this research into two parts, a theoretical aspect to study the role of total productivity, and inflation in determining wages , An applied aspect of a Standard Study of the impact of each on the nominal wages in the Algerian economic sector. The results showed the existence of a co-integration relationship in the long run between total productivity, inflation rate and nominal wages through the Bounds test, It also showed an estimate in the long run on the existence of a positive relationship between the total productivity of the economic sector, the rate of inflation and nominal wages